Prevalência de crianças com dificuldades motoras em Fortaleza/CE - Santos, Letícia Rodrigues Vieira (2018)
The objective of the present study was to identify the prevalence of motor difficulties in a sample of children from Fortaleza/CE and to identify in which motor components these difficulties are more evident. Four hundred and twenty-three children aged 7 to 10 years old, both sexes from elementary school, participated in the present study. Participants were assessed by the Movement Assessment Battery for Children – 2 (MABC-2) and identified with Motor Difficulty (MD), Risk at motor difficult and Typical Development (TD). Statistical analyzes were used to show the prevalence of children identified with TD, Risk and DM, to identify the differences between the sexes in this distribution and the scores on the motor components (Manual dexterity, Throw and Receive and Balance) and on the total MABC-2. The results showed 11,6% of the children were identified with DM and 25,8% were identified at Risk for motor difficulties. Although there was no difference between the prevalence of girls and boys identified with DM, girls performed better than boys in the Manual dexterity and Balance components of MABC-2, while boys performed better than girls on the Throw and Receive component of MABC-2. These results lead to the discussion that environmental factors, related to the socio-cultural context, can influence children’s motor development. In addition, it was possible to observe that the prevalence of children identified with DM in Fortaleza is similar to that found in the literature in other Brazilian regions. This prevalence is worrisome, considering the damages and problems caused by the difficulties, including the probable Developmental Coordination Disorder (DCD). Identify children with motor difficulties helps in the process of intervention and care so that they can have a complete motor development.